The Electoral System of the US: Reform Proposals from a Political Economy Point of View - Friedrich L. Sell; Jürgen Stiefl (CESifo Forum, 2022)
The US, one of the oldest democracies in the world, needs to face deficiencies in its electoral system. The first one has to do with the so-called 'Electoral College.' Ruled by the majority principle, it may lead to almost paradoxical results: a candidate may win far less than 50 percent of the popular vote share and yet be elected as US President. The second one is located in the 'geography' of the elections for the House of Representatives, organized in the federal states. Surprisingly, the likelihood for winning a district is, to a large extent, dependent on its geographical design and allocation. Thereby, it is possible for even minority parties to take advantage and win the majority of representatives ('gerrymandering'). We discuss both of these problematic aspects of the US electoral system and put forward some alternatives to improve the situation from a political economy point of view.
Keywords: 330